Prevalence and severity of neurologic symptoms in Long-COVID and the role of pre-existing conditions, hospitalization, and mental health - Hanalise V. Huff; Henry Roberts; Elizabeth Bartrum; Gina Norato; Nicholas Grayson; Katherine Fleig; Miciah J. Wilkerson; Barbara J. Stussman; Avindra Nath; Brian Walitt (Frontiers in Neurology)
BackgroundLong-COVID refers to ongoing, relapsing, or new symptoms present 30 or more days after Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. This study examined the prevalence and severity of neurologic symptoms at greater than 1 month following acute SARS-CoV-2 infection and the influence of pre-existing neurologic and psychiatric conditions, current depression and anxiety status, and hospitalization on the presence and severity of these symptoms.MethodsThis prospective cohort study recruited primarily self-referred Long-COVID participants with confirmed SARS-CoV-2 infection. Online questionnaires inquiring about pre-existing conditions, neurologic symptoms and their severity pre, during and post COVID-19, and current anxiety and depression screening were completed by 213 participants at a median time of 8 months after infection. Descriptive analyses and prevalence modeling were performed.ResultsThe most frequent neurologic symptoms post COVID-19 were fatigue, concentration/memory difficulties, unrefreshed sleep, and dysarthria/word finding difficulties (73.2–86.4%). Neurologic symptoms were highly prevalent with significantly greater odds post COVID-19 compared to pre for all symptoms and higher prevalence at time periods farther from infection, including those implicit in fibromyalgia and myalgic encephalomyelitis/chronic fatigue syndrome. Several severe neurologic symptoms were significantly more prevalent post COVID-19. Moderate to severe anxiety (34%) and depression (27%) were observed post COVID-19. Preexisting neurologic or psychiatric conditions did not demonstrate any significant difference in neurologic symptom prevalence post COVID-19. Those who met criteria for moderate or severe anxiety post COVID-19 had a significant difference in prevalence of fatigue, sensitivity to touch and unrefreshed sleep. Similarly, fatigue, concentration/memory difficulty and unrefreshed sleep were more prevalent in moderate to severe depression. There were no significant differences in neurologic symptom prevalence in a hospitalized group when compared to non- hospitalized.ConclusionLong-COVID has a high burden of long lasting and severe neurological sequelae. These sequelae are independent of pre-existing self-reported neurologic and psychiatric conditions, as well as previous hospitalization. Current moderate to severe anxiety and depression status can impact fatigue, cognition, and sleep post COVID-19. Focus on the biological impact of SARS-CoV-2 on the nervous system will be essential in ameliorating the tremendous symptom burden left in the wake of the COVID-19 pandemic.Clinical trial registrationhttp://clinicaltrials.gov, identifier: NCT04573062.